An Investigation of Students' Writing Skills: A Study of The Four-Square Writing Approach - Muslaini, Fadel; Amiruddin, Amiruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The purpose of this study is to see if using the 4-square method improves the writing skills of IAI As'adiyah Sengkang's fifth-semester English students. A pre-experimental design was used in this study. The population of this study was IAI As'adiyah Sengkang's English education. The data was gathered using the pre-test and post-test methods. The findings of this study show that the 4-Square approach considerably improved the writing skills of IAI As'adiyah Sengkang's English education. This was demonstrated by the paired-sample t-test result, which revealed that the probability value (0.00) was less than the level of significance (0.05), showing a significant difference between the pre-test and post-test findings. As a result, the 4-square technique helped pupils enhance their writing skills in terms of grammar, content, punctuation, and spelling.